The Clinical Significance of CYP450 in Gastrointestinal Tract - Neneng Ratnasari (The Indonesian Society for Digestive Endoscopy, 2007)
Cytochromes P450 (CYP450) is a super-family of multigenes bound to heme and also a catalysator enzyme. Cytochrome P450s (1, 2, and 3) are the most important enzymes for biotransformation of drugs administered through gastrointestinal tract. The gastrointestinal tract is the first part of immune system against all of oral xenobiotics. Drug interaction may be predicted but it is hardly prevented. Thus, it frequently becomes clinical problem. CYP450 polymorphism may influence effective drug metabolism, which consequently will affect drug response and good therapeutic effect. Poor metabolizers need only a small dose of drug to bring on drug response but extensive or ultra-rapid metabolizers will need a large dose of drug. The unexpressed CYP2E1, one of the CYP families, may influence cancer incidence. However, it is still controversial. Keywords: CYP450, xenobiotics, biotransformation of drugs, gastrointestinal tract